The HIV Paradox: Acquired Immunodeficiency, Latent Reservoirs, and Mechanisms of Viral Persistence - Barack Ndenga (Publisher, 2026)
Despite more than four decades of intense research and the remarkable success of combination antiretroviral therapy(cART) in suppressing viral replication, HIV infection remains incurable. The virus persists in a stochastic archipelago of long-lived cellular reservoirs that evade immune surveillance and therapeutic intervention, guaranteeing viral recrudescence upon treatment cessation. This fundamental paradox—effective suppression without eradication—represents the central impediment to a cure. In this review, we deconstruct the biological and immunological architecture of HIV persistence. We focus on the establishment and maintenance of latent reservoirs, the pharmacological blind spot of current therapies, and the conceptual frameworks that distinguish viral control from clearance. Decoding these mechanisms is an essential predicate for the rational design of next-generation curative strategies. Keywords : HIV persistence,HIV latency,Viral reservoir,HIV cure,Antiretroviral therapy,CD4+ memory T cells,Provirus,Immunological sanctuary,Clonal expansion,Functional cure,Shock and kill,Post-treatment control,Viral pathogenesis,Immunology,Infectious diseases
Why Antiretroviral Therapies Fail to Achieve a Curative Outcome
Despite the transformative success of combination antiretroviral therapy(cART) in controlling HIV replication, infection remains incurable due to the persistence of latent, replication-competent viral reservoirs. This review articulates the central paradox of HIV management—effective suppression without eradication—by deconstructing the biological and immunological architecture of viral persistence. We examine the establishment of latent proviruses within long-lived CD4+ memory T cells and anatomically privileged sanctuary sites, mechanisms that render these reservoirs invisible to both antiretroviral drugs and immune surveillance. The analysis details the pharmacological and immunological limitations of current therapies, distinguishing between the concepts of sterilizing cure and functional remission. By synthesizing foundational and contemporary research, this work provides a critical framework for understanding the barriers to an HIV cure and establishes the conceptual prerequisites for the rational design of next-generation curative strategies, including latency reversal, immune engineering, and reservoir mapping.